Protective Effect of Tyrosol on BALF Cytology and Biochemistry in Rats Administered Intratracheal Bleomycin - Ekinci, Elif; Karabulut, Burak; Incili, Canan Akdeniz; Cankaya, Eren; Seker, Ibrahim; Timurkaan, Necati (Mdpi, 2025)
This study aimed to investigate the cytological and biochemical effects of tyrosol on bronchoalveolar lavage fluid (BALF) in an experimental lung injury model induced via intratracheal bleomycin (BLM) administration at 4 mg/kg. Tyrosol is a compound found in olive oil with antioxidant, anti-inflammatory, and antifibrotic activity, and there are no publications on its effect on broncho-alveolar lavage. A total of fifty male Sprague Dawley rats were randomly divided into five groups: control, BLM only, and BLM combined with tyrosol at doses of 20, 40, and 80 mg/kg. Following a two-week treatment period, BALF samples were collected and evaluated cytologically and biochemically. BLM administration led to significant increases in the proportions of lymphocytes, neutrophils, and epithelial cells (p < 0.05) and a decrease in macrophage percentages in BALF. Tyrosol treatment modulated these cellular alterations in a dose-dependent manner, with notable increases in macrophage ratios and reductions in inflammatory cells, particularly at 40 and 80 mg/kg doses. Furthermore, the presence of foamy macrophages-commonly observed in the BLM group-was found to decrease in a dose-dependent manner with tyrosol administration. Biochemical analyses showed that BLM significantly elevated malondialdehyde (MDA) levels (p < 0.05), while reducing the levels of antioxidant enzymes such as superoxide dismutase (SOD), glutathione peroxidase (GPx), and catalase (CAT). Tyrosol treatment improved these parameters in a dose-dependent manner, thereby reducing oxidative stress. In cytokine analysis, BLM increased all proinflammatory cytokine levels, whereas tyrosol treatment, particularly at higher doses, significantly decreased IL-6 levels (p < 0.05). In conclusion, tyrosol demonstrated notable protective effects against bleomycin-induced lung injury by exerting anti-inflammatory and antioxidative actions at the BALF level.
Keywords: bleomycin; BALF; foamy macrophage